Effectiveness of Badan Penasihat Pembinaan dan Pelestarian Perkawinan in the Prospective Bride Course Program as an Effort to Anticipate Divorce - Adaham Asparoni Nasution; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Divorce and marital disputes are significant social issues in Deli Serdang Regency, Indonesia. This study evaluates the effectiveness of the prospective bride and groom course program and the role of the Marriage Counseling, Guidance, and Preservation Agency (BP4) in resolving marital disputes during the 2021-2023 period. This empirical legal research employs a descriptive qualitative approach, utilizing data from BP4 statistical reports and the Lubuk Pakam Religious Court. The findings indicate that BP4's involvement in marital disputes is low, ranging from 0.95% to 1.48% of total cases filed with the Religious Court, but the success rate of mediation at BP4 is significant, reaching 33.33%. The prospective bride and groom course program is effective in reducing the number of disputes that end up in court. Policy recommendations include increasing public awareness about the importance of mediation before filing court cases and strengthening the prospective bride and groom course program as a more effective divorce prevention measure.